Consequences of a high phosphorus intake on mineral metabolism and bone remodeling in dependence of calcium intake in healthy subjects – a randomized placebo-controlled human intervention study - Trautvetter, Ulrike; Jahreis, Gerhard; Kiehntopf, Michael; Glei, Michael (Nutrition journal, 2016)
Epidemiological studies reported an association between plasma phosphate concentrations and a higher risk for death and cardiovascular events in subjects free of chronic kidney diseases. The main aims of the present study were to determine the influence of a high phosphorus intake in combination with different calcium supplies on phosphorus, calcium, magnesium and iron metabolism as well as fibroblast growth factor 23 (FGF23) concentrations within eight weeks of supplementation. Sixty-two healthy subjects completed the double-blind, placebo-controlled parallel designed study. Supplements were monosodium phosphate and calcium carbonate. During the first two weeks, all groups consumed a placebo sherbet powder, and afterwards, for eight weeks, a sherbet powder according to the intervention group: P1000/Ca0 (1 g/d phosphorus), P1000/Ca500 (1 g/d phosphorus and 0.5 g/d calcium) and P1000/Ca1000 (1 g/d phosphorus and 1 g/d calcium). Dietary records, fasting blood samplings, urine and fecal collections took place. Fasting plasma phosphate concentrations did not change after any intervention. After all interventions, renal excretions and fecal concentrations of phosphorus increased significantly after eight weeks. Renal calcium and magnesium excretion decreased significantly after eight weeks of P1000/Ca0 intervention compared to placebo. Plasma FGF23 concentrations were significantly higher after four weeks compared to eight weeks of all interventions. The long-term study showed in healthy adults no influence of high phosphorus intakes on fasting plasma phosphate concentrations. A high phosphorus intake without adequate calcium intake seems to have negative impact on calcium metabolism. Plasma FGF23 concentrations increased four weeks after high phosphorus intake and normalized after eight weeks. The trial is registered at ClinicalTrials.gov as NCT02095392 .